Neuroimaging in paediatric emergencies - Tanmayi, Uppalapati; G., Abhinaya; E., Adarsh; M., Gautam (International Journal of Advances in Medicine, 2023)
Background: Neonatal and Pediatric population comprise up to 20% of emergencies and it is very important to choose appropriate imaging modality to diagnose early and treat accurately. These Pediatric emergencies require different approach to diagnose and manage compared to the adult population. This article will focus on the neuroimaging for evaluation and diagnosis that has more common and specific occurrence in paediatric population. Methods: Cases were selected based on inclusion and exclusion criteria and a single centre study was done using the scanners, imaging software and medical records from March 2021 to August 2022. Results: 36 non-traumatic cases were further subgrouped based on the etiological factors; of which 13 cases (36.1%) had findings consistent with congenital abnormalities. The proportion of children with Hypoxic ischemic encephalopathy, Stroke, Infections and Neoplastic were 10 cases (27.7%), 9 cases (25%), 5 cases (13.8%), 4 cases (11.1%) and 4 cases (11.1%) respectively. Conclusions: Neuroimaging is the key in pediatric emergencies. The advancement in newer modalities of technology should be put into use more as a combined approach in diagnosis, management and prognostication as well as for early intervention to improve functional and psychological outcome.